2017
DOI: 10.1149/2.0381712jes
|View full text |Cite
|
Sign up to set email alerts
|

Impedance Spectroscopy Analysis of the Lithium Ion Transport through the Li7La3Zr2O12/P(EO)20Li Interface

Abstract: Model systems for electrochemical impedance spectroscopy (EIS) studies of solid-state electrolytes based on ceramic lithium ion conductor Li 7 La 3 Zr 2 O 12 (LLZO) and polymer electrolyte P(EO) 20 -LiClO 4 are investigated for the first time. The aim of the present study is to identify and quantify the lithium ion transition resistance of the ceramic/polymer interface. Symmetrical model systems consisting of LLZO pellets with sheets of P(EO) 20 -LiClO 4 are manufactured and investigated in detail. In such sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 50 publications
(58 reference statements)
2
48
0
Order By: Relevance
“…The activation energy of the PE/SE interface in case of lithium-ion conductors is determined around 1 eV in three independent studies with different PE/SE combinations [52,55,58]. For example, Abe et al investigated the interface between LLTO and PEO complexed with LiTf using twopoint EIS measurements [52].…”
Section: Solid/polymer Interfacesmentioning
confidence: 99%
See 3 more Smart Citations
“…The activation energy of the PE/SE interface in case of lithium-ion conductors is determined around 1 eV in three independent studies with different PE/SE combinations [52,55,58]. For example, Abe et al investigated the interface between LLTO and PEO complexed with LiTf using twopoint EIS measurements [52].…”
Section: Solid/polymer Interfacesmentioning
confidence: 99%
“…In a recent study [58], it was shown that a porous interface str ucture between LLZO and PEO 20 ∶LiClO 4 (EO∶Li + = 20∶1) resulted in a significantly increased resistance while the activation energy was similar to the LLTO/PE discussed above [52]. Fitting the recorded EIS data with a de Levie element-a transmission line model generally used for porous electrodes [68,69]-enabled the distinction between pore and ion transition contributions [58].…”
Section: Solid/polymer Interfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the scattering pattern of linear PEO may also exhibit other Bragg reflections such as (024) and (131) at 26.4° and 27.1°, in our results they are not notable. When adding LLZO into PEO, more peaks also arise as LLZO has a cubic garnet structure such as at 16.6°, 25.6°, 27.4°, and 19.3° which overlaps PEO. Comparison of WAXS spectra of crystallized PEO and LLZO particles can be found in the Supporting Information Figure S4.…”
Section: Resultsmentioning
confidence: 99%